INVESTIGATION OF REACTION SPEED OF THE STUDENTS WHO DO SPORT AND DO NOT IN THE AGE GROUP OF 12-18 (Journal of Pharmaceutical Negative Results, 2022)
Objective: Our research aimed to examine the reaction speed of 12-18 year old students who do sports and those who do not. Material and Methods: A total of 427 students participated in the study, with the participation of 263 boys and 164 girls, aged 12-18, who continue their education in primary and secondary schools in Van. In order to measure the visual and auditory reaction rates, the "Newtest 1000" reaction device was adjusted in 00.01 milliseconds. SPSS package program was used in the data. In analysis, Mann Whitney U for paired comparisons, Kruskall-Wallis H test for multiple comparisons and descriptive statistics were used. The level of significance was determined as P˂0.05.Results: Exercising regularly (p=0.000), using technology intensively (Right-left hand visual p=0.000, Right hand auditory p=0.002, Left hand auditory p=0.001, Right hand mixed p=0.007, Left hand mixed p=0.000), gender (p=0.000), leisure-time situations (Right hand visual p=0.013, left hand visual p= 0.000, Right hand auditory p=0.006, left hand auditory p=0.102, Right hand mixed p=0.049 There was a significant difference between the left hand mixed (p=0.002) and reaction rates. There was a significant difference in left hand auditory reaction rates of individuals who do individual and team sports in favor of those who do individual sports (p=0.023). There was no difference between students' ages, parental education levels, dominant hand, body mass index, daily television watching time, wearing glasses, academic achievement and visual and auditory reaction rates (P>0.05). Conclusion: It has been observed that regular exercise has a positive effect on increasing reaction speed.